Enhancing the Strength and Durability Behaviour of Concrete Produced with Brown-Loamy Kaolin Clay Polymer - Patrick Zievie; Peter Paa-Kofi Yalley; Humphrey Danso; Kwaku Antwi (Journal of Building Materials and Structures)
Clay is the most utilised natural pozzolana in Ghana, with the red-loamy clay in southern Ghana being the most widely studied. It has been established that clays geographical location presents differences in their optimum calcination temperatures and cement replacement levels. The aim of this study was to investigate the potential use of brown-loamy kaolin clay polymer in northern Ghana as a natural pozzolana. The clay was thermally activated, and it became more pozzolanic reactive at 800oC. The clay was used to replace cement at 0%, 5%, 10%, 15% and 20% based on the weight of the cement, and denoted as Ao, K5, K10, K15 and K20 respectively. Concrete cubes of size 150×150×150mm and cylinders of size 150×300mm were cast and cured for 7, 14, 28, and 90 days. The samples were tested for density, compressive strength, split tensile strength, water absorption and sulphate attack. Maximum compressive and split tensile strengths were achieved at the 15% replacement level in all curing durations. Again, there was a significant decrease in water absorption and sulphate attack up to the 15% replacement level. Beyond the 15% and up to the 20%, the decrease was minimal. The increase in strength and decrease in durability properties was significantly high in 90 days compared to 7 days. The study therefore recommends the use of brown-loamy clay up to 15% cement substitution. It use would be advantageous for concrete production in situations where high to medium workability and delays in setting times are required.